INFLASI INDONESIA DALAM KURUN WAKTU 2 DEKADE TERAKHIR DAN FAKTOR-FAKTOR YANG MEMPENGARUHI - Ilham Tri Murdo; Redy Herinanto Albertus; Junaidi Affan; Ch. Dini Ika Handayani (Juremi: Jurnal Riset Ekonomi, 2024)
This research aims to determine the extent to which independent variable factors (GDP, Amount of Money in Circulation (JUB), Exchange Rate and Interest Rates) influence the dependent variable (Inflation) over the last 24 years. Quantitative research aims to obtain empirical evidence regarding the influence of the variables GDP, Money Supply (JUB), Exchange Rate and Interest Rates on Exports, and also test hypotheses to strengthen or even reject the hypothesis. With the following results: Gross Domestic Product (GDP) has the opposite relationship and has no effect on Inflation, Money Supply has a positive and significant effect on Inflation. The exchange rate has an inverse relationship and has no effect on inflation. Interest rates have an inverse, influential and significant relationship to inflation. Gross Domestic Product (GDP), money supply (JUB), exchange rate and interest rates together (simultaneously) have a significant and significant influence on inflation